Comparative macrogenomics reveal plateau adaptation of gut microbiome in cervids - Bin Li; Yuangang Yang; Bo Xu; Pengfei Song; Feng Jiang; Hongmei Gao; Zhenyuan Cai; Haifeng Gu; Tongzuo Zhang (BMC Biology)
Abstract Background Diverse gut microbiota in animals significantly influences host physiology, ecological adaptation, and evolution. However, the specific functional roles of gut microbiota in facilitating host adaptation, as well as the coevolutionary dynamics between microbiota and their hosts, remain largely understudied. Results A total of 41,847 metagenome-assembled genomes and 3193 high-quality species-level genome bins were generated, establishing a comprehensive gut microbiome catalog for cervids in this study. Phylogenetic analysis revealed a coevolutionary relationship between cervids and their gut microbiota. Comparative metagenomic analyses further indicated that the gut microbiota of plateau cervids have undergone genome-level adaptations related to energy metabolism. At the genus level, species-level genome bins from the genera Alistipes and Faecousia in plateau cervids exhibit enhanced energy metabolism capabilities. Structural variations analysis revealed that the insertion and duplications structural variations in the gut microbiota of plateau cervids were significantly enriched in energy metabolism pathways. In contrast, the deletions and contractions in structural variations were predominantly enriched with metabolic pathways involved in the biosynthesis of diverse biochemical molecules. Conclusions Our study provides a comprehensive gut microbiome catalog of the cervid gut microbiota, revealing the coevolutionary relationship between cervid gut microbiota and hosts. These findings highlight the adaptive genomic evolution of the gut microbiota in contributing to the plateau adaptability of cervids and offer new insights into the mechanisms by which the gut microbiota help hosts adapt to extreme environments.